(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
In this article, one of the most important issues in Uzbek linguistics is the different views of Uzbek scientists on the division of parts of words into categories. We witness the work of our scientists that scientific research has been carried out on the basis of the theme from simplicity to complexity in the separation of categories. It is recognized that the influence of European and Russian linguists on the improvement of Uzbek modern morphology and parts of speech is also significant. However, we can assume that the development of science as a result of the influence of fraternal and lateral languages has been a process that has been proven for several centuries.